2010
DOI: 10.1016/j.ijpharm.2010.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biophysical characterization of lysozyme modified by PEGylation

Abstract: PEGylation is a strategy that has been used to improve the biochemical properties of proteins and their physical and thermal stabilities. In this study, hen egg-white lysozyme (EC 3.2.1.17; LZ) was modified with methoxypolyethylene glycol-p-nitrophenyl carbonate (mPEG-pNP, MW 5000). This PEGylation of LZ produced conjugates that retained full enzyme activity with glycol chitosan, independent of degree of enzyme modification; its biological activity with the substrate Micrococcus lysodeikticus was altered accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 49 publications
2
28
0
2
Order By: Relevance
“…The apparent molecular weight of the different PEGylated species obtained from size exclusion chromatography and gel electrophoresis (SDS-PAGE) is overestimated due to the retarded mobility of PEGylated proteins, which has been previously reported [56], [57]. Moreover, it has also been reported that a 5 kDa-PEG-conjugated protein increases its apparent molecular weight in 15 kDa approximately [58]. This phenomenon has been attributed to the fact that the hydrodynamic volume for a PEG-conjugated protein results higher than the expected for a protein of similar molecular weight, due to the high hydrophilicity of the PEG unit [59], [60].
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…The apparent molecular weight of the different PEGylated species obtained from size exclusion chromatography and gel electrophoresis (SDS-PAGE) is overestimated due to the retarded mobility of PEGylated proteins, which has been previously reported [56], [57]. Moreover, it has also been reported that a 5 kDa-PEG-conjugated protein increases its apparent molecular weight in 15 kDa approximately [58]. This phenomenon has been attributed to the fact that the hydrodynamic volume for a PEG-conjugated protein results higher than the expected for a protein of similar molecular weight, due to the high hydrophilicity of the PEG unit [59], [60].
Fig.
…”
Section: Resultsmentioning
confidence: 98%
“…PEGylated G-CSF (Neulasta), for example, retains 41% of its native enzymatic activity. 11 Prior studies with lysozyme conjugated to a 5 kDa PEG chain showed suppressed enzymatic activity (77%) relative to the native enzyme, 49 whereas a study on polyMPC-BSA and lysozyme conjugates showed 75−90% of native enzymatic activity. 26 These data suggest that polymer conjugation does not markedly reduce enzyme activity but that a modest reduction in activity may result from polymer shielding effects (steric interference).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This effect can be mitigated via chemical modification of the protein, for example the covalent attachment of a hydrophobic dye or the polymer polyethylene glycol (PEG) (Lee et al, 2015). However, the reaction products can be difficult to separate, require extensive filtration or chromatography to remove unreacted components, and result in substantial purification loss (Freitas and Abrahão-Neto, 2010; Lee et al, 2003). One of the advantages of utilizing HME as an alternative to solvent based encapsulation methods is the increased encapsulation efficiency, scale-up potential, and solventless nature (Maniruzzaman et al, 2012; Repka et al, 2012).…”
Section: Introductionmentioning
confidence: 99%